Inclusão de estudantes com deficiência nas instituíções de ensino superior da cidade do Natal/RN:análise das condições oferecidas no processo seletivo vestibular - Santos, Andreza Souza (2012)
The number of disabled students, who have entered the university, in Brazil, since the beginning of this century, is undergoing a speed growth. It is a change that follows a global trend that spreads an inclusive education policy and that has had a profound impact on Brazil, with import results in field researches. This subject has been highlighted due to the significant amount of disabled students enrolled in college institutions (IES), although it is still modest the number of studies about it, especially in what matters the assistance given to the candidates to a university entrance examination. The aim of this paper is to investigate how effectively Natal s IES apply the rules established in Brazilian law concerning disabled students, especially MEC/GM Circular Warning n. 277/96, in what respects the conditions given to disabled students preparing to enter a college. The investigation followed a qualitative methodological approach with support on an exploratory study. The data recollection employed questionnaire, semi-structured interview and documental analyses, and the data have been organized and assessed following Minayo s (1996) stages. What concerns the results, it was observed that none of the ten colleges inquired confirmed to possess places exclusively to disabled candidates; six of them, however, offer Special Examining Board in the selection process of disabled candidates. Among eighteen college bills, only two of them offered specific information related to services and resources offered by IES to the candidates who ask for especial assistance concerning examination. During the interviews, four managers avowed the preoccupation in offering an equal selection process, but two of them proved not dominate the subject. In conclusion, the investigated institutions managers do not still seem to respect the rule that guarantees to disabled candidates equal conditions during all the process of the university entrance examination. With this work, we hope do help changing this focus and contribute to new studies on disabled persons studying for a degree